What antihypertensive agents are least likely to cause erectile dysfunction?. Issue 6 (June 2015) - Battjes, Edward; Harsh, Katie; Langton, Elizabeth; Huber, Brian
Abstract : Evidence‐Based Answer : Certain β‐blockers and chlorthalidone, when prescribed for hypertension, are associated with an increased incidence of erectile dysfunction (ED), while other classes of antihypertensive agents are not (SOR: B, meta‐analysis, RCTs).